Threshold effects of inflation on growth in the ASEAN-5 countries: A Panel Smooth Transition Regression approach - Thanh, Su Dinh (2015)
The relationship between inflation and economic growth is a contentious issue. The present study is undertaking to test hypothesis that the relationship between inflation and economic growth is nonlinear. This pane data study involves ASEAN-5 countries over the period 1980–2011. Panel Smooth Transition Regression (PSTR) model is employed to estimate the threshold of inflation and its effects on economic growth. Furthermore, we also check robustness by using GMM-IV specification. The study finds that there exists a statistically significant negative relationship between inflation and growth for the inflation rates above the threshold level of 7.84%, above which inflation starts impeding economic growth in the ASEAN-5 countries. The results suggest that central banks in the ASEAN-5 countries could improve economic growth by reducing inflation when it is above or near the estimated thresholds. The threshold inflation level can be considered, therefore, as inflation targeting indicator to conduct monetary policy. Doi: http://dx.doi.org/10.1016/j.jefas.2015.01.003